Susac Syndrome: A Case Series - Hoogewoud, Florence; Kawasaki, Aki; Borruat, François-Xavier; Guex-Crosier, Yan (Klinische Monatsblätter für Augenheilkunde, 2022)
Background Susac syndrome (SS) is an autoimmune disorder that involves the eyes, the brain, and the ears. It is a rare cause of recurrent branch retinal artery occlusion. The purpose of this study was to report cases of SS, highlighting the clinical presentations, therapeutic options, and their outcome.Patients and Methods Retrospective case series of patients seen at our institution for SS between 2005 and 2020. Demographics, clinical characteristics, treatment, and outcome were studied.Results Four patients (3 females, mean age 29 years old) were included in the study. According to the recently revised diagnostic criteria, three patients had definite and one patient had probable SS (distinctive ophthalmological and brain involvement without ear involvement). Initial visual acuity (VA) was normal in all eyes, but two patients had unilateral visual field impairment. Gass plaques (defined as yellow-white plaques found in the arteriolar wall away from arterial bifurcations) were observed on fundus examination in all patients. Fluorescein angiography revealed arteriolar wall hyperfluorescence and branch retinal arterial occlusions (BRAOs) in the absence of other signs of intraocular inflammation in all patients. Initial treatment consisted of a high-dose corticosteroid (intravenous or oral) with additional immunosuppressive therapy (azathioprine, intravenous immunoglobulins, mycophenolate mofetil, and/or cyclophosphamide). Residual symptoms were present in all patients and included scotoma (n = 2) and hearing loss (n = 3).Conclusion SS is a rare disease with characteristic ophthalmological manifestation. The majority of patients present a crude form of the triad, and retinal findings may be the first initial manifestation. Ophthalmologists should consider the possibility of an SS in all young patients presenting with BRAOs.
Keywords: SICRET; branch retinal artery occlusion; cerebral vasculitis; perceptive hypoacusis; retinocochleocerebral vasculopathy; posterior uveitis